Complete step-by-step guide to cake decorating - Deacon, Carol (London : New Holland, 2003)
"Gives beginners cake recipes and step-by-step instructions on how to use buttercream frosting, fondant, royal icing, and marzipan to decorate them"--
Baking basics -- Cake recipes -- Number and letter cakes -- Basic equipment -- Buttercream frosting -- Fondant -- Marzipan -- Royal icing -- Chocolate -- Substitutions -- Suppliers.
Includes index.
Keywords: Cake decorating; Cookbooks